2022
DOI: 10.3390/v14050958
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamics of Mexican Lineage H5N2 Avian Influenza Viruses

Abstract: We have demonstrated for the first time a comprehensive evolutionary analysis of the Mexican lineage H5N2 avian influenza virus (AIV) using complete genome sequences (n = 189), from its first isolation in 1993 until 2019. Our study showed that the Mexican lineage H5N2 AIV originated from the North American wild bird gene pool viruses around 1990 and is currently circulating in poultry populations of Mexico, the Dominican Republic, and Taiwan. Since the implementation of vaccination in 1995, the highly pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
(88 reference statements)
0
0
0
Order By: Relevance
“…Notably, the newly glycosylated residues are close to antigenic sites B and E. Im-mune pressure has played a vital role in viral antigenic evolution and residue glycosylation. The same scenario has been shown in the Mexican H5N2 LPAIV evolutionary analysis [62].…”
Section: Discussionsupporting
confidence: 69%
“…Notably, the newly glycosylated residues are close to antigenic sites B and E. Im-mune pressure has played a vital role in viral antigenic evolution and residue glycosylation. The same scenario has been shown in the Mexican H5N2 LPAIV evolutionary analysis [62].…”
Section: Discussionsupporting
confidence: 69%
“…The absence of anti-hemagglutinin activity or features in this mAb might have contributed to its broader reactivity spectrum, which is possibly due to a smaller burden of immune selection pressure on its binding epitope. Studies have shown that frequent residue alterations at the HA antigenic sites were observed with vaccinations implemented in poultry [32,33]. Thus, if the mAb epitope is within the antigenic sites, it has more chance to lose reactivity due to antigenic evolution.…”
Section: Discussionmentioning
confidence: 99%